The Principle of Legal Balance and the Degradation of Incentive Rights in Protected Rice Field Policies - Mohammad Habib Ramdhani; Iwan Permadi; Indah Dwi Qurbani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The increasing conversion of paddy fields to non-agricultural uses poses a significant threat to national food security, prompting the Indonesian Government to enact Presidential Regulation Number 4 of 2026 concerning the Control of Paddy Field Conversion. This regulation introduces a protection mechanism through the designation of Protected Paddy Fields (LSD) and imposes restrictions on landowners' rights to convert their agricultural land. As a balancing instrument, the regulation also provides incentives for individuals who maintain the agricultural function of their land. However, the incentive provisions contained in Articles 20 and 21 raise normative concerns, particularly due to the phrase "subject to the State's financial capacity," which creates legal uncertainty. This study aims to analyze the juridical implications of the ambiguity of the incentive provisions on the legal certainty of Protected Paddy Field owners and to assess their conformity with the principles of balance and proportionality in administrative law. The research employs a normative legal method using statutory, conceptual, and analytical approaches. The findings reveal that the phrase constitutes a vague norm because it fails to specify the parameters of the State's fiscal capacity, the mechanism for granting incentives, or the legal consequences of the State's failure to provide them. As a result, the public's right to receive incentives becomes uncertain, while the restrictions on land conversion rights apply directly and are legally binding. This situation creates an asymmetric legal relationship between the State and landowners, indicating that the incentive provisions under Presidential Regulation Number 4 of 2026 do not fully satisfy the principles of legal certainty, balance, and proportionality. Therefore, a normative reconstruction is necessary to ensure the certainty of incentive implementation as a form of legal protection for landowners affected by controlling policies the conversion of paddy fields.